1981
DOI: 10.1007/bf03007148
|View full text |Cite
|
Sign up to set email alerts
|

Regional analgesic effect of epidural morphine in volunteers

Abstract: Limb ischaemia induced by a sub-maximum effort tourniquet technique was used to characterize the analgesic effects of lumbar epidural morphine in volunteers. As an index of pain threshold, we measured the time to perception of pain in an upper and a lower limb before and at intervals up to six hours following epidural injections of morphine 3.5 mg and 7.0 rag, and before and after subcutaneous injections of the same doses. Subcutaneous morphine had no significant effect on the times to perception of pain in ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Onset of analgesic effect in humans has been repeatedly reported to be approximately 30 minutes after epidural morphine administration, with a peak effect at approximately 50 to 90 minutes. [29][30][31] The effect on MAC might, however, be independent of the analgesic effect and, therefore, have a different onset time. From published studies 11,12,22 that revealed an effect of morphine on MAC and in which onset can be assessed, it appears that onset occurred 30 to 100 minutes after administration.…”
Section: Discussionmentioning
confidence: 99%
“…Onset of analgesic effect in humans has been repeatedly reported to be approximately 30 minutes after epidural morphine administration, with a peak effect at approximately 50 to 90 minutes. [29][30][31] The effect on MAC might, however, be independent of the analgesic effect and, therefore, have a different onset time. From published studies 11,12,22 that revealed an effect of morphine on MAC and in which onset can be assessed, it appears that onset occurred 30 to 100 minutes after administration.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, extradural morphine 3.5 or 7.5 mg markedly delayed the onset of experimentally induced ischaemic pain in the lower limbs, but not in the arms. This effect was still present 6h after injection [185]. Subcutaneous morphine had no significant effect on the times to pain perception in either limb and the authors concluded that the extradural morphine produced analgesia by a regional effect rather than by systemic absorption.…”
Section: Analgesic Effectsmentioning
confidence: 92%
“…In non-pregnant women, extradural morphine alone provides a long-lasting analgesia of slow onset. In pregnant women, extradural morphine alone, in a dose of 5 mg or less, is ineffective in providing satisfactory pain relief throughout labour [1,3,[5][6][7][8][9], probably because the extradural vascular congestion of pregnancy enhances vascular absorption of morphine [18][19][20][21][22][23][24]. Several investigators have reported that extradural bupivacaine improves the quality of analgesia when administered after [9] or simultaneously with [12] extradural morphine during the first stage of labour.…”
Section: Discussionmentioning
confidence: 99%